Can We Improve the Tolerance of an Ocular Prosthesis by Enhancing Its Surface Finish?. Issue 2 (March 2018) - Litwin, Andre S.; Worrell, Emma; Roos, Jonathan C. P.; Edwards, Barry; Malhotra, Raman
Abstract : Purpose: Patients who wear an ocular prosthesis frequently suffer with dry eye symptoms and socket discharge, often on a daily basis. The aim of the study was to determine whether a smoother, optical quality polish of the prosthesis' surface could improve symptoms and wear tolerance. The study was designed as single-center, single-masked, prospective randomized controlled trial. Eighty-eight consecutive patients undergoing annual ocular prosthesis maintenance review were approached from the prosthesis clinic. Forty-one out of 49 eligible patients were recruited. Methods: Participants were randomized to either a standard or a higher "optical quality" polish of their prosthesis. At entry to the trial, at 1 month, and 12 months they completed a questionnaire covering cleaning, lubricant use, inflammation, discomfort, and discharge. Lower scores indicated better tolerance of the prosthesis. At each visit, the prosthesis was stained and photographed against a standard background to assess deposit build up. Primary outcome measures were 1) a subjective questionnaire score and 2) an objective assessment of surface deposit build-up on prosthetic eyes by standardized photographic grading. Results: Forty-one patients participated in the study. The median age of their prosthesis was 36 months (range 9 months–40 years). There was no statistically significant difference in questionnaire scores or deposit build up between the 2 groups at baseline. By 12-months, the higher optical quality polish showed a statistically significant reduction in symptoms and frequency of discharge (2.19 vs. 3.85; p = 0.05—lower scores better). Scoring of the prosthesis' deposit build-up showed a significant difference at 1 month, but this was not sustained at 12 months. Conclusions: Creating an optical quality finish to an ocular prosthesis reduces deposit build up on artificial eyes. The authors found this modification improved patient tolerance at 12 months. Abstract : In this randomized controlled trial, enhanced polishing of ocular prostheses using aluminum oxide achieved a smoother surface, resulting in reduced deposit build-up and fewer patient-reported discomforts.